A Maximum Principle via Malliavin calculus for combined stochastic control and impulse control of forward‐backward systems. Issue 5 (1st February 2015) - Wang, Yan; Song, Aimin; Feng, Enmin
Abstract We consider a combined stochastic control and impulse control problem of forward‐backward systems driven by Lévy processes, where both the system coefficients and the objective performance functional are allowed to be random, non‐Markovian; the information available to the controller is partial information. Applying a Malliavin calculus approach, we derive a maximum principle for this control problem, where the adjoint processes are explicitly represented by the parameters and the states of the system. Finally, we give two examples of applications. © 2015 Chinese Automatic Control Society and Wiley Publishing Asia Pty Ltd